A Cross-Sectional Analysis of Knowledge, Beliefs and Practices Regarding Traditional Medicine Use among Pharmacy Students of Different Private and Government Universities of Lahore, Pakistan (Bangladesh Journal of Medical Science, 2022)
Background: Students’ understanding regarding traditional medicine is a part of pharmacy curriculum. In Pakistan, be it students or healthcare professionals, little is known about the general importance of traditional medicine.Objectives: The aim of this study is to assess the students, enrolled in Doctor of Pharmacy Program, regarding their beliefs, knowledge and practices for use of medicinal plants.Methodology: The questionnaires were distributed among the Doctor of Pharmacy (Pharm-D) students. The data was analyzed using SPSS software (IBM, version. 22) and different statistical tests were applied, including descriptive analysis, t-test and Pearson chi squared test.Results: Total 254 responses were obtained in the study. While the outcome indicates that the majority of the participants (n=237: 93.3%) acknowledge the usefulness of traditional medicine. 151 (59.4%) participants believed that the traditional medicine is safe but 103 (40.6%) concerned about the side effects of herbal remedies. 187 (73.6%) reported the use of some type of medicinal plants in their life. Easy availability of traditional medicine was reported by 186 (73.2%) participants and 176 (69.3%) claimed the medicinal plants as inexpensive alternatives. The physician was kept informed about the concomitant administration of herbal with allopathic medicine in only 43 (16.9%). Stomach pain (14.17%) was most common sickness for which participants utilized traditional treatment, followed by cough (12.6%) and flu (10.63%). Mint (10.24%) was found to be the most commonly used medicinal plant, followed by aloe (9.84%) and ginger (7.48%).Conclusion: Detailed studies are still required to evaluate not only the students but also health care professionals about their understanding, prescribing practice and dealing with patients already using medicinal plants. This will help in improved management of the disorders and may lead further advancement in the field of natural product research and cutting off ill effects of allopathic treatment.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 323-334